PENDIDIKAN KOGNITIF DAN AFEKTIF DAGUSIBU UNTUK PENCEGAHAN RESISTENSI ANTIBIOTIK DI SMA SURABAYA - Abhimata Paramanandana; Dini Retnowati; Andang Miatmoko; Dewi Isadiartuti; Sugiyartono1; Mohammad Agus Sjamsur Rijal; Dwi Setiawan; Esti Hendradi; Tutiek Purwanti; Noorma Rosita; Dewi Melani Hariyadi; Tristiana Erawati; Ardhani Dwi Lestari1; Helmy Yusuf; Retno Sari (Talenta Publisher, 2019)
Antibiotics are not only used for humans, but also often used for cattle and livestock which are then been consumed by humans. This over prescribed and missed used of antibiotic is a major factor in antibiotic resistance. Antibiotic resistance is a condition where bacteria are unable to be treated with antibiotics. In fact, the use of antibiotics is the first response in curing infectious diseases (by bacteria) and preventing infectious diseases spreading. With antibiotic resistance, preventing infectious diseases by bacteria became harder. This community service activity came up with a slogan